Fundamentals of Risk Management for Accountants and Managers - Collier, Paul M. M (Elsevier, 2011)
Both financial and non-financial managers with accountability for performance at either a strategic level or for a business unit have responsibility for risk management, in terms of failing to achieve organisational objectives. Fundamentals of Enterprise Risk management is structured around four parts and 26 self-contained chapters. Each chapter will have ample practical examples and illustrations/mini-case studies from retail, manufacturing and service industries and from the public and not-for-profit sectors to enable the reader to understand and apply the concepts in the book.